PENGEMBANGAN MEDIA GAME EDUKASI ONLINE DENGAN PLATFORM GAMIFIKASI PADA MATA PELAJARAN INFORMATIKA DI SEKOLAH MENENGAH PERTAMA NEGERI 3 MATTIROBULU - Sudirman, Sirajuddin; Ruslan; Djawad , Yasser Abdul (UNM Journal of Technology and Vocational, 2024)
This research aims to: (1) Describe the stages of developing an online educational game media design with a gamification platform in informatics subjects in junior high schools, (2) Develop an online educational game media with a gamification platform in informatics subjects in junior high schools that is valid for use based on experts, (3) Developing online educational game media with a gamification platform in informatics subjects in junior high schools that is practical for use in the classroom, (4) Developing online educational game media with a gamification platform in informatics subjects in junior high schools which effective in completing learning achievements. The type of research used is research & Development. The research sample consisted of 40 class VII students at UPT SMP Negeri 3 Mattirobulu. Data collection techniques use questionnaires, interviews and observations. The research results are: (1) Developing online educational game media with a gamification platform at State Junior High School 3 Mattirobulu include in 5 stages that is, Analysis, Design, Development, Implementation and Evaluation, (2) Online educational game media with a gamification platform is declared valid for use based on scores from media experts with an average score of 88.8 and material experts with an average score of 90.3 with both being in very valid criteria, (3) Online Educational Game Media with a Gamification Platform is declared practical to use based on the average results from teachers assestment was 87.2 and from students was 84.2, both of which were in the very practical category, and (4) Online Educational Game Media with a gamification platform effectively improved student learning outcomes as seen from the results of the pre-test and post-test resulting in N-Gain high scores that has 0.72 which is in the high category.